"Reconstruc+ons of the past distribu+on of Testudo graeca mitochondrial lineages in the Middle East and Transcaucasia support mul+ple refugia since the Last Glacial Maximum": A response to Turkozan et al. (2021). Issue 4 (October 2021) - Ihlow, Flora; Fritz, Uwe; , Peter Mikulíček; Rödder, Dennis
No abstract available